Cell Adhesion on Nanometer Scale Protein Patterns With Micrometer Scale Spacings - Vurmaz, Deniz; Pesen Okvur, Devrim; Oyman, Gizem; Okvur, Devrim Pesen (American Society for Cell Biology, 2012)
[No abstract available]